2011
DOI: 10.1007/s11065-011-9182-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Differences Between Patients with Left-sided and Right-sided Parkinson’s Disease. A Review

Abstract: At disease onset, patients with Parkinson's disease (PD) typically report one side of the body to be more affected than the other. Previous studies have reported that this motor symptom asymmetry is associated with asymmetric dopaminergic degeneration in the brain. Research on the cognitive repercussions of this asymmetric degeneration has yielded inconsistent results. Here, we review studies that reported on the cognitive performance of patients with left-sided (LPD) or right-sided (RPD) motor symptom predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 75 publications
8
81
1
Order By: Relevance
“…Furthermore, FER deficit could also be linked to motor asymmetries in PD, but the question of whether patients with left‐dominant motor symptoms (LPD) showing relatively greater neural degeneration in the right hemisphere have a more severe deficit than patients with right‐dominant motor symptoms remains open. LPD patients could be more likely to show FER impairments considering the relatively greater role of the right hemisphere in FER (at least for anger, fear, and sadness) and the prominence of visuospatial deficits in LPD patients 85, 86. Last, since the earliest studies, emotional disorders in PD concern both expression and recognition, and some authors have even reported positive correlations between facial expression and FER impairment 17, 37, 87, 88, 89.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…Furthermore, FER deficit could also be linked to motor asymmetries in PD, but the question of whether patients with left‐dominant motor symptoms (LPD) showing relatively greater neural degeneration in the right hemisphere have a more severe deficit than patients with right‐dominant motor symptoms remains open. LPD patients could be more likely to show FER impairments considering the relatively greater role of the right hemisphere in FER (at least for anger, fear, and sadness) and the prominence of visuospatial deficits in LPD patients 85, 86. Last, since the earliest studies, emotional disorders in PD concern both expression and recognition, and some authors have even reported positive correlations between facial expression and FER impairment 17, 37, 87, 88, 89.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…This is due to greater degeneration of dopaminergic neurons in the dorsal striatum of the brain hemisphere contralateral to the body's side‐of‐onset (Donnemiller et al., 2012). This asymmetric depletion leads to further dysfunction of the neural circuits connected to the basal ganglia, which influence cognitive abilities (Verreyt et al., 2011). Additionally, it has been reported that brain asymmetry may have a role in emotion and/or motivation (Fetterman, Ode, & Robinson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that brain asymmetry may have a role in emotion and/or motivation (Fetterman, Ode, & Robinson, 2013). Based on this asymmetrical degeneration, much research has focused on the cognitive/neuropsychological and even clinical differences between LOPD and ROPD (e.g., Verreyt et al., 2011). However, recent research has suggested that the cognitive differences are not seen in the recently diagnosed, unmedicated, early stage of PD, such as those in Hoehn and Yahr (H&Y) Stage 1 (Erro et al., 2013; Pellicano et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations